Neuronal nicotinic acetylcholine receptor antibodies in autoimmune central nervous system disorders - Pechlivanidou, Maria; Vakrakou, Aigli G.; Karagiorgou, Katerina; Tüzün, Erdem; Karachaliou, Eleni; Chroni, Elisabeth; Afrantou, Theodora; Grigoriadis, Nikolaos; Argyropoulou, Christina; Paschalidis, Nikolaos; Şanlı, Elif; Tsantila, Aikaterini; et al. (Frontiers in Immunology, 2024)
Background: Neuronal nicotinic acetylcholine receptors (nAChRs) are abundant in the central nervous system (CNS), playing critical roles in brain function. Antigenicity of nAChRs has been well demonstrated with antibodies to ganglionic AChR subtypes (i.e., subunit α3 of α3β4-nAChR) and muscle AChR autoantibodies, thus making nAChRs candidate autoantigens in autoimmune CNS disorders. Antibodies to several membrane receptors, like NMDAR, have been identified in autoimmune encephalitis syndromes (AES), but many AES patients have yet to be unidentified for autoantibodies. This study aimed to develop of a cell-based assay (CBA) that selectively detects potentially pathogenic antibodies to subunits of the major nAChR subtypes (α4β2- and α7-nAChRs) and its use for the identification of such antibodies in “orphan” AES cases. Methods: The study involved screening of sera derived from 1752 patients from Greece, Turkey and Italy, who requested testing for AES-associated antibodies, and from 1203 “control” patients with other neuropsychiatric diseases, from the same countries or from Germany. A sensitive live-CBA with α4β2-or α7-nAChR–transfected cells was developed to detect antibodies against extracellular domains of nAChR major subunits. Flow cytometry (FACS) was performed to confirm the CBA findings and indirect immunohistochemistry (IHC) to investigate serum autoantibodies’ binding to rat brain tissue. Results: Three patients were found to be positive for serum antibodies against nAChR α4 subunit by CBA and the presence of the specific antibodies was quantitatively confirmed by FACS. We detected specific binding of patient‐derived serum anti‐nAChR α4 subunit antibodies to rat cerebellum and hippocampus tissue. No serum antibodies bound to the α7-nAChR-transfected or control-transfected cells, and no control serum antibodies bound to the transfected cells. All patients positive for serum anti‐nAChRs α4 subunit antibodies were negative for other AES-associated antibodies. All three of the anti‐nAChR α4 subunit serum antibody-positive patients fall into the AES spectrum with one having Rasmussen encephalitis, another autoimmune meningoencephalomyelitis and another being diagnosed with possible autoimmune encephalitis. Conclusions: This study lends credence to the hypothesis that the major nAChR subunits are autoimmune targets in some cases of AES and establishes a sensitive live-CBA for the identification of such patients.